The Effectiveness Of Using The Meta Cognition Strategies In Teaching Mathematics On The Development Of Systemic Thinking Among The Basic Ninth Grade Students - Khalil Al-qaisi, Taiseer (European Scientific Journal, ESJ, 2016)
This study aimed to investigate the effectiveness of using the meta cognition strategies in teaching mathematics on the development of systemic thinking among the basic ninth grade students in Tafila Governorate. The sample of this study consisted of two female groups; experimental and control were selected from Tafila basic school for girls, and another two male groups; experimental and control were selected from Omar bin Alkhattab basic school for Boys. The analysis unit to factors and fractures was selected; teacher's guide was prepared to be used as a teaching guide. Achievement test was set up to measure the systemic thinking among the study sample, where its reliability and validity were also confirmed. The results indicated that the level of systemic thinking did not reach the level of mastery of 75%; where the average of the scores of the experimental group students was 25.28, which is considered less than proposed average of the level of mastery of 30, and with statistical significance, and with statistically significant differences between the mean scores of individuals in experimental and control groups in favor of the experimental group, and that there are statistically significant differences between males and females in favor of females. In light of these findings, the study recommends training the teachers on these strategies, and using the meta cognition teaching when developing the curricula. In addition, it recommends conducting similar studies on other variables such as creative thinking, critical thinking, and attitudes towards mathematics.